2016
DOI: 10.1007/s10534-016-9945-1
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the cytotoxic implications of metal chelators against melanoma and approaches to improve the cytotoxicity profiles of metal coordinating agents

Abstract: The cytotoxic activity of thiosemicarbazones (TSC) and thiocarbohydrazones was investigated against the MelRm melanoma cell line. In general, the melanoma line was susceptible to metal coordinating agents, the most useful of which incorporated the dipyridyl ketone hydrazone sub-structure. The impact of copper supplementation on the cytotoxic activity towards the melanoma line (MelRm) of metal coordinating agents when acting as ionophores is less predictable than the general improvement that has been seen in ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Finally, another study has shown that a different class of metal chelators (i.e. thiosemicarbazones) have the ability to induce cytotoxicity on melanoma cells by disrupting the cellular antioxidant defence system thus causing elevation of intracellular ROS levels [74].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, another study has shown that a different class of metal chelators (i.e. thiosemicarbazones) have the ability to induce cytotoxicity on melanoma cells by disrupting the cellular antioxidant defence system thus causing elevation of intracellular ROS levels [74].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it has been reported that Dp44mT and their complexes with iron and copper cause apoptosis by generating cytotoxic ROS [ 23 , 40 ]. Moreover, Akladios et al reported that in some TSC, the addition of metal cations may increase activity [ 41 , 42 ]. This observation led to the alternative use of TSC as ionophores.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, DMSO − water mixtures are widely used in biological studies serving as a proper solvent for several biomolecules such as flavins, carotene, etc. (Akladios et al 2016 ; Rajniak et al 2018 ; Tsai et al 2018 ). However, the possibility of iron complexation by the solvent ligands is normally not considered in these studies.…”
Section: Introductionmentioning
confidence: 99%